A novel natural mutation AαPhe98Ile in the fibrinogen coiled-coil affects fibrinogen function - Riedelová-Reicheltová, Zuzana; Kotlín, Roman; Suttnar, Jiří; Geierová, Věra; Riedel, Tomáš; Májek, Pavel; Dyr, Jan Evangelista (Thrombosis and Haemostasis, 2014)
The aim of this study was to investigate the structure and function of fibrinogen obtained from a patient with normal coagulation times and idiopathic thrombophilia. This was done by SDS-PAGE and DNA sequence analyses, scanning electron microscopy, fibrinopeptide release, fibrin polymerisation initiated by thrombin and reptilase, fibrinolysis, and platelet aggregometry. A novel heterozygous point mutation in the fibrinogen Aα chain, Phe98 to Ile, was found and designated as fibrinogen Vizovice. The mutation, which is located in the RGDF sequence (Aα 95–98) of the fibrinogen coiled-coil region, significantly affected fibrin clot morphology. Namely, the clot formed by fibrinogen Vizovice contained thinner and curled fibrin fibers with reduced length. Lysis of the clots prepared from Vizovice plasma and isolated fibrinogen were found to be impaired. The lysis rate of Vizovice clots was almost four times slower than the lysis rate of control clots. In the presence of platelets agonists the mutant fibrinogen caused increased platelet aggregation. The data obtained show that natural mutation of Phe98 to Ile in the fibrinogen Aα chain influences lateral aggregation of fibrin protofibrils, fibrinolysis, and platelet aggregation. They also suggest that delayed fibrinolysis, together with the abnormal fibrin network morphology and increased platelet aggregation, may be the direct cause of thrombotic complications in the patient associated with pregnancy loss.
Keywords: Fibrinogen; platelet aggregation; RGD sequence; thrombosis; pregnancy loss